2020
DOI: 10.1021/acs.langmuir.0c00787
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Fluorescence Quantification of Hydrolytic Enzyme Activity on Native Substrates Reveals How Lipase Function Depends on Membrane Curvature

Abstract: Lipases are important hydrolytic enzymes used in a spectrum of technological applications, such as the pharmaceutical and detergent industry. Due to their versatile nature and ability to accept a broad range of substrates they have been extensively used for biotechnological and industrial applications. Current assays to measure lipase activity primarily rely on low sensitivity measurement of pH variations or visible changes on material properties, like hydration, and often require high amount of proteins. Fluo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Glass surfaces were prepared using plasma cleaned glass slice with fastened sticky-Slide VI 0.4 (Ibidi) and functionalized using PLL-g-PEG and PLL-g-PEG-biotin in a 100 to 1 ratio followed by a neutravidin layer 36 , 37 . Each glass surface contains 6 chambers that are independently utilized for liposomes immobilization and imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Glass surfaces were prepared using plasma cleaned glass slice with fastened sticky-Slide VI 0.4 (Ibidi) and functionalized using PLL-g-PEG and PLL-g-PEG-biotin in a 100 to 1 ratio followed by a neutravidin layer 36 , 37 . Each glass surface contains 6 chambers that are independently utilized for liposomes immobilization and imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Hundreds of liposomes per field of view were tethered on poly( l ‐lysine)‐poly(ethylene glycol) (PLL‐PEG)‐passivated and PLL‐PEG biotin‐passivated surfaces [23, 24] . This methodology maintains the spherical shape and structural integrity of the liposomes [25] .…”
Section: Resultsmentioning
confidence: 99%
“…The parallel readout and analysis of hundreds (>700) of individual liposomes on six surfaces before and after Na 2 EDTA addition allowed us to quantify the fraction of 1⋅Zn liposomes the responded to Zn 2+ removal [23, 25, 26] . It was found that 65.0±4.4 % of the liposomes were active and responded to Na 2 EDTA (Figure 3 g).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence microscopy is a powerful and sensitive detection tool [17][18][19] , but its capability for multiplexing is limited by the spectral overlap between chromophores, restricting quantitative imaging to a handful of fluorescent colors 20,21 . Fluorescent barcoding technologies can overcome this, offering some success in multiplexing for both in vitro and in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The method combines chromophore ratio labelling creating distinct identity encoding barcodes for each DNA encoded nanocontainer and the use of complementary LiNA mediated nanocontainer fusion. Using TIRF microscopy allowed the parallelized imaging of ~8800 individual target lipidic containers [17][18][19]28,29 undergoing >16,000 fusion events with barcoded cargo nanocontainers and up to seven successive rounds of fusion. The fusion sequence is completely stochastic allowing >550 distinct permutations that are directly recorded and precisely classified by machine learning analysis.…”
Section: Introductionmentioning
confidence: 99%